2014
DOI: 10.1186/s12870-014-0264-9
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation and cellular toxicity of aluminum in seedling of Pinus massoniana

Abstract: BackgroundMasson pine (Pinus massoniana) is one of the most important timber species with adaptable, fast growing, versatile advantages in southern China. Despite considerable research efforts, the cellular and molecular mechanisms of A1 toxicity and resistance in P. massoniana are still poorly understood. The effects of Al on uptake and translocation of Al and other minerals, cell division and nucleolus in P. massoniana were investigated.ResultsThe results indicated that Al accumulated mainly in the roots, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
31
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 67 publications
3
31
0
8
Order By: Relevance
“…Jiang et al [3] found that MTs of Allium cepa root meristem cells under heavy metal Pb stress changed significantly with increasing Pb concentrations and prolonged treatment times, cortical MT appeared depolymerization, adhesion, compaction, and mitotic spindle arrangement appeared disorder, even leading to chromosome abnormal separation, seriously influencing the cell cycle. Zhang et al [7] studied the effect of aluminium (Al) on masson pine root meristem cell MTs, which was consistent with the research results before [34]. Heavy metals could lead to significant changes in the cytoskeleton, hindering normal cell differentiation and proliferation.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Jiang et al [3] found that MTs of Allium cepa root meristem cells under heavy metal Pb stress changed significantly with increasing Pb concentrations and prolonged treatment times, cortical MT appeared depolymerization, adhesion, compaction, and mitotic spindle arrangement appeared disorder, even leading to chromosome abnormal separation, seriously influencing the cell cycle. Zhang et al [7] studied the effect of aluminium (Al) on masson pine root meristem cell MTs, which was consistent with the research results before [34]. Heavy metals could lead to significant changes in the cytoskeleton, hindering normal cell differentiation and proliferation.…”
Section: Discussionsupporting
confidence: 67%
“…Chromosome stickiness was considered to be a chromatid-type aberration and was attributed to the effect of environmental pollutants on degredation or depolymerization of chromosomal DNA, on DNA condensation, and on entanglement of intertions between chromosomes [3]. The chromosome aberration might be the effect of Cd on DNA and RNA synthesis [7]. It was well known that MTs play key roles in both nuclear division and mitosis in plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the discrepancy between our results with the CHO A L assay and those of other assays that are best at detecting base level damage, is likely due to aluminium's association with larger, chromosomal‐level alterations. Indeed, it is well‐known that aluminium causes chromosomal aberrations in plants . Similarly aluminium‐associated aberrations have also been observed in grasshopper spermatocytes and in the bone marrow of injected mice .…”
Section: Discussionmentioning
confidence: 97%
“…O Al interfere na divisão celular das células do ápice da raiz principal e nas raízes laterais, aumenta a rigidez da parede celular através da reticulação de pectinas e reduz a replicação de DNA por causar rigidez na dupla hélice (ZHANG et al, 2014). Estudos indicam que o Al pode limitar o crescimento de espécies importantes para a arborização urbana.…”
Section: Introductionunclassified